PENGARUH PEREBUSAN BIJI MELINJO (Gnetum gnemon L) TERADAP KUALITAS SENSORIS EMPING MELINJO - Yulpin Sasea; Judith S.C. Moningka; Christine F. Mamuaja; Teltje Koapaha (COCOS, 2015)
ABSTRACTMelinjo (Gnetum gnemon L) has many benefits. Besides as a food ingredient, melinjo also contain antioxidant compounds. This research aimed to test the sensory properties of melinjo which includes color, aroma, flavor and crispness. The benefits of this research can provide information to the public about the influence of boiling beans melinjo against melinjo sensory test and its content. The research was conducted in the village Nunu Rainis District of Talaud Islands and the Department of Agricultural Technology Laboratory for 2 months. The design used was a completely randomized design (CRD) with four long boiling treatment, ie A = 5 minutes, B = 10 min, C = 15 min, D = 20 minutes. The best test of the sensory panelists obtained in boiling for 20 minutes treatment (treatment D), the chemical content as follows: 11:38% moisture content, ash content 0.79%. 1:45% fat content, protein content 14:12%, 72.26% carbohidrat levels.Keywords: Gnetum gnemon L, Crackers, Sensoric